2013
DOI: 10.15381/rpb.v20i1.2613
|View full text |Cite
|
Sign up to set email alerts
|

The Jack mackerel Trachurus murphyi in Peru

Abstract: es_ES), que permite el uso no comercial, distribución y reproducción en cualquier medio, siempre que la obra original sea debidamente citadas. Para uso comercial, por favor póngase en contacto con

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…and in the present work; changes in their diet should then indicate changes in the ecosystem. Indeed JM abundance and biology is known to be affected by climatic regime (Csirke, 2013). Here we showed that changes in prey contribution actually corresponded to observed changes in the ecosystem in the case of P. monodon but not for euphausiidae.…”
Section: Long Term Trend and The Euphausiidae Paradoxsupporting
confidence: 52%
“…and in the present work; changes in their diet should then indicate changes in the ecosystem. Indeed JM abundance and biology is known to be affected by climatic regime (Csirke, 2013). Here we showed that changes in prey contribution actually corresponded to observed changes in the ecosystem in the case of P. monodon but not for euphausiidae.…”
Section: Long Term Trend and The Euphausiidae Paradoxsupporting
confidence: 52%
“…Furthermore, there is ample evidence that Spanish colonization changed the Peruvian seascape. By the time Spaniards arrived in Peru, the Inca Empire (1,000–1,532 CE) had incorporated the coastal adoration of the sea as a central part of their Andean ideology (Cobo, 1653/1964). Also, the allocation of area‐based fishing rights was the mechanism by which the Incas controlled fishing efforts (Rostworowski, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Jack mackerel (Trachurus murphyi) is one the most exploited oceanic species and the third largest fishery in Peru (Csirke, 2013). It has been hypothesized that heavy exploitation in the high seas during the last two decades conducted to a reduction of the abundance of existing subpopulations in the whole South Pacific Ocean (Canales, 2014).…”
Section: Introductionmentioning
confidence: 99%